Transformative Learning in AIK Learning: Strategies to Improve Students' Religious and Critical Literacy in the Era of Pop Culture and Social Media - Muhammad Rifki Hidayat; Mhd. Lailan Arqam (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The phenomenon of pop culture and social media has become an integral part of student’s lives, influencing their ways of thingking, values, and daily behaviors. The Al-Islam and Muhammadiyah Studies (AIK) course plays an essential role in strengthening students’ religious and critical literacy to respond to contemporary challenges. This study aims to examine the application of Transformative Learning in AIK as a strategy to develop student’s religious and critical literacy in the era of pop culture and social media. This research employs a qualitative method with a library research approach through analysis of scientific literatur, books, and relevant journal articles. The result show that AIK learning based on Transformative Learning encourages student to engage in deep reflection, critique assumption, and internalize religious values amidst rapid information flow. This approach not only enhances cognitive understanding of religion but aslso shapes student into religious and critical change agents. The study recommends integrating contemporary issues into AIK to improve learning relevance and meaningfulness.